RESPON PERTUMBUHAN DAN HASIL KEDELAI EDAMAME (Glycine max) PADA BERBAGAI DOSIS PEMBERIAN NPK MULTIPADI DAN KASGOT - Anastasia Jessika Devi; Djoko Heru Pamungkas; Darnawi (JURNAL ILMIAH AGROUST, 2026)
This study aims to investigate the interaction between NPK Multi-rice and Kasgot doses, as well as to determine their optimal levels to enhance the growth, quality, and yield of Edamame soybeans.This research was conducted from October to December 2024 in Agromulyi Village, Sedayu Distric, Bantul Regency, Special Region of Yogyakarta. The research location is in a lowland area with altitude of 80-105 meters above sea level (masl), average daily temperatures ranging from 21- 32°C, relative humidity 70-90%, and annual rainfall around 1,500-2,500 mm. This study was compiled in a Group Random Design with 3 replicates. This first factor is that the dose of Kasgot fertilizer consists of 3 levels, namely 0 ton/ha, 1,25 ton/ha and 2,5 ton/ha. The second factor is that the Multi-rice NPK consists of 3 levels, namely 300 kg/ha, 400 kg/ha and 500 kg/ha. The variables observed ware plant height, number of leaves, fresh weight of plants, dry weight of plants, number of pods, fresh weight of pods, number of seeds, weight of 100 seeds and yield of tons/hectare. Data analysis uses fingerprints at the 5% level, followed by DMRT at the 5% level. The results showed that the interaction between Kasgot and NPK Multipadi fertilizers had a significant effect on the number of leaves, number of pods, 100-seed weight, and pod yield per hectare. Individually, Kasgot fertilizer significantly affected nearly all growth and yield variables, with the best results observed at a dose of 2.5 tons/ha. NPK Multipadi fertilizer also had a significant effect on several variables, including plant height, number of leaves, number of pods, 100-seed weight, and pod yield per hectare. However, no significant effects either from interaction or individual treatments were found on plant height, fresh and dry plant weight, fresh pod weight, and number of seeds.